2020
DOI: 10.4314/aas.v17i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Meckel’s diverticulum with acute appendicitis in an infant

Abstract: Meckel's diverticulum occurs in approximately 2% of the population and is symptomatic in 16% of cases. In children, the most common presentation is intestinal obstruction due to intussusception. The simultaneous occurrence of acute appendicitis and symptomatic Meckel's diverticulum is rare and when it occurs, it may be associated with non-specific symptoms that present a diagnostic challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Jumbi et al reported also a concomitant presentation of acute appendicitis and perforated Meckel's diverticulitis in an infant. It was clinically presented at first with intestinal obstruction and later on complicated with such perforation [8] . Different approaches were described in the literature to manage Meckel's diverticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Jumbi et al reported also a concomitant presentation of acute appendicitis and perforated Meckel's diverticulitis in an infant. It was clinically presented at first with intestinal obstruction and later on complicated with such perforation [8] . Different approaches were described in the literature to manage Meckel's diverticulum.…”
Section: Discussionmentioning
confidence: 99%